Magnetic Nanocomposites from Rice Husk Ash for Heavy Metal Adsorption in Groundwater - Fadhilah Nur Afifah; Salsabilla; Hanifah Sriamelia (Science Journal Get Press, 2026)
Heavy metal contamination in groundwater poses serious risks to human health and ecosystems, requiring effective and sustainable remediation strategies. This study reports the synthesis of magnetic nanocomposites derived from rice husk ash (RHA) and Fe₃O₄ nanoparticles for the removal of Pb(II), Cd(II), Cr(VI), and As(V). RHA, a silica-rich agricultural waste, was converted into nano-silica via alkaline extraction and combined with Fe₃O₄ through co-precipitation. The synthesized nanocomposites were characterized using XRD, FTIR, SEM-EDX, BET, and VSM, confirming a high surface area (254.8 m²/g), strong magnetization (38.7 emu/g), and nanoscale particle size (10.3 nm). Batch adsorption experiments under optimal conditions (pH 6.0, contact time 120 min, adsorbent dose 1.0 g/L) showed removal efficiencies exceeding 90% for all metals. Maximum adsorption capacities based on the Langmuir model were 204.1 mg/g for Pb(II), 158.3 mg/g for Cd(II), 179.6 mg/g for Cr(VI), and 132.9 mg/g for As(V). Kinetic analysis followed a pseudo-second-order model, indicating chemisorption. The nanocomposites also demonstrated good reusability over five cycles, highlighting their potential as low-cost, eco-friendly adsorbents for groundwater treatment.